Metode Matrix Morfology Untuk Perancangan Bangun Alat Perakit Knob Switch Assy Electric Park Brake Module - A Wahyu Cahyo Purnomo; Oktavianus Ardhian Nugroho; Eustachius Dwi Septiawan (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
Press Machine For Switch Assy EPB module is an SPM (Special Purpose Machine) with a special function to carry out the pressing process of EPB (Electric Park Brake) products, namely an electronically controlled parking brake, where the driver activates the restraining mechanism with a button. So far, the epb product assembly process uses a manual mechanism by pressing the parts of the operator. This process is still not optimal, therefore it requires the development of a new EPB assembly system to improve and achieve maximum production processes. In this paper, an EPB product pressing system has been made using a jig. The jig is designed and manufactured using a photoelectric sensor integrated with the PLC. This study aims to improve the Quality Assurance of each EPB product and increase productivity to be more stable. The previous EPB product assembly process was carried out manually by the operator and there were often errors in the form of installation discrepancies in the process. In this paper, a press has been designed and made with sequential system operation with a ladder language program stored in a PLC. Sequential will run based on limit switches and photoelectric triggers to detect every product that enters the pressing process. The results of this study the quality and efficiency of the EPB assembly process increased where the human error that caused product failure was reduced, besides that the tools made had advantages among idle time in the EPB production process could be minimized.